Coupling and power transfer efficiency enhancement of modular and array of planar coils using in-plane ring-shaped inner ferrites for inductive heating applications - Kilic, V. T. (2017)
We propose and demonstrate a highly effective method of enhancing coupling and power transfer efficiency in inductive heating systems composed of planar coils. The proposed method is based on locating ring-shaped ferrites in the inner side of the coils in the same plane. Measurement results of simple inductive heating systems constructed with either a single or a pair of conventional circular coils show that, with the in-plane inner ferrites, the total dissipated power of the system is increased by over 65%. Also, with three-dimensional full electromagnetic solutions, it is found that power transfer efficiency of the system is increased up to 92% with the inner ferrite placement. The proposed method is promising to be used for efficiency enhancement in inductive heating applications, especially in all-surface induction hobs.